Aflatoxin B1 exposure increases the risk of hepatocellular carcinoma associated with hepatitis C virus infection or alcohol consumption. (May 2018) - Chu, Yu-Ju; Yang, Hwai-I; Wu, Hui-Chen; Lee, Mei-Hsuan; Liu, Jessica; Wang, Li-Yu; Lu, Sheng-Nan; Jen, Chin-Lan; You, San-Lin; Santella, Regina M.; Chen, Chien-Jen
Abstract: Background: Hepatocarcinogenicity of aflatoxin B1 (AFB1 ) has rarely been studied in populations with hepatitis C virus (HCV) infection and those without hepatitis B virus (HBV) and HCV infection (non-B-non-C). This case-control study nested in a community-based cohort aimed to investigate the HCC risk associated with AFB1 in HCV-infected and non-B-non-C participants. Methods: Baseline serum AFB1 -albumin adduct levels were measured in 100 HCC cases and 1767 controls seronegative for anti-HCV and HBsAg (non-B-non-C), and another 103 HCC cases and 176 controls who were anti-HCV-seropositive and HBsAg-seronegative. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were estimated using logistic regression. Results: In 20 years of follow-up, the follow-up time to newly developed HCC was significantly shorter in participants with higher serum AFB1 -albumin adduct levels in non-B-non-C ( p  = 0.0162) and HCV-infected participants ( p  < 0.0001). Within 8 years of follow-up, HCV infection and AFB1 exposure were independent risk factors for HCC. Elevated serum AFB1 -albumin adduct levels were significantly associated with an increased risk of HCC newly developed within 8 years of follow-up in non-B-non-C participants with habitual alcohol consumption [crude OR (95% CI) for high vs. low/undetectable levels, 4.22 (1.16–15.37)] and HCV-infected participants [3.39 (1.31–8.77)], but not in non-B-non-C participants without alcohol drinking habit. AFB1 exposure remained an independent risk predictor for HCV-related HCC after adjustment for other HCC predictors (multivariate-adjusted OR [95% CI], 3.65 [1.32–10.10]). Conclusions: AFB1 exposure contributes to the development of HCC in participants with significant risk factors for cirrhosis including alcohol and HCV infection. Highlights: Effect of Aflatoxin B1 (AFB1 ) in hepatitis C virus (HCV)-related and non-viral HCC has rarely been studied. AFB1 increases HCC risk in participants with habitual alcohol drinking and HCV infection. The follow-up time to HCC diagnosis was significantly shorter in participants with higher AFB1 exposure.